A tortura aos presos políticos durante a ditadura militar brasileira: uma abordagem psicanalítica - Figueiredo Filho, Celso Ramos (2009)
Torture was widely used by military dictatorship (1964-1985) to repress opposition politicians, mainly in order to obtain, in a short time, information about political underground organizations. In this scene of horror, the figure of the torturer stands out. Who is this man? Why does he torture? Social sciences, in general, have much contributed to the understanding of such phenomenon, although, due to their epistemological limits, they do not approach the subjective scope of torture. Certainly we do not ignore that man is a social being. In fact we have started from the premise that human nature lies in its social "excentration" and so we refute the works that psychologize social events. The psychoanalysis used here starts from the same premise and attempts to understand the often conflicting relation between subject and collectivity. It does not ignore, then, neither social nor subject. The torturers identified themselves exactly as in Freud's description (1921): by making the same object took the place of an ideal "I". This object could be either a General Commander, or the idea of "saving the country", or the usual values of capitalism, such as "status" and material benefits. At the same time, the ideal of "I" could be the group itself, that is, the mere fact of belonging to a fraternity. A social arrangement in which neurotics shared the illusion of having a single "Other" was supported by that identification. In exchange for the alienation of that arrangement, that is, the submission to a supposed "Other", neurotics experienced a jouissance which they would not have by themselves in the banality of their symptoms. As each subject refers to his own "Other", each one provides his own jouissance with different discourse positions, all of them belonging to the same arrangement. So, according to Lacan's theory of "The Four Discourses", torturers wavered between the "Discourse of the Master", the one that "only wants things to work", that is, the commanding position, and the "Discourse of the University". In that position, the military officers' speech was based on the "National Security and Development Doctrine" (Doutrina de Segurança Nacional e Desenvolvimento - DSN), a position intended to stand above each subject's particularity, thus standing on a false "neutrality". DSN was the ideological sustentaion for the regime. Its outstanding elements were a Brazilian Army's particular concept of Positivism, that of national authoritarian thinkers and General Góes Monteiro's doctrinarism, as well as elements of cold war ideology. Psychoanalysis considers ideology as a "social fantasy", that works as a barrier to "Real", in this case, class struggles, while it signs as a promise of collective jouissance.Thus, a subject, driven by the fantasy of a"revolutionary war" and a "subversive enemy", joins the setting and gives himself permission to torture and to kill. So, the typical capitalism subject, with his controlled jouissance, subjected to the setting and identified with signifiers of bourgeois ideology fantasy, such as individualism and materialism, did not hesitate about turning the other into an object: the threatening "strange". This one, having a different jouissance, revealed a structural failure, a hole in the chain of signifiers. And, in face of the horror of truth, he projected that horror on to the other, and attributed to the other an evil that allowed him to torture and to kill the other. The sadic jouissance of torture is, paradoxically, the only trace of humanity that remains in the torturer after his total alienation